Sexual dysfunction in Iraqi women with breast cancer and undergoing chemotherapy - Alaa Abdulrazzaq Alanbagi (International Journal of Research in Pharmaceutical Sciences, 2023)
Breast cancer has been identified as one of the leading non-skin cancers for women in North America and the UK as well. Studies have also pointed out that women from all over the world are at equal threats of developing breast cancer. This study was aimed to determine the factors influencing breast cancer and corresponding treatment effects on sexual dysfunction. This study took into account 48 cancer patients that have undergone surgery and chemotherapy within last year. Data for comparison regarding incident rate was acquired from the Iraqi Cancer Registry covering a period of 4 years from 2011 to 2014. The treatment sample was obtained for Al-Sadder Medical City, Najaf, Iraq, and experiences related to cancer and its treatment correlated with sexual activity. The investigation was seen to be the situation by just half of the members. Notwithstanding, preceding the investigation, it was seen that 36% of the example of 48 had begun to encounter sexual brokenness before treatment. Concerning the present conditions, 47% of the members revealed they had dropped their sexual want amid the beginning of the condition until the beginning of treatment. Another 39% asserted that it has quit having intercourse following agony amid intercourse (Dyspareunia) it reasoned that age alone had a task to carry out in light of menopause given the high pervasiveness of bosom malignant growth among 50+ years' people. Based on these observations, this study concludes that sexual dysfunction among Iraqi women is a direct influence by the cumulative breast cancer diagnosis and treatment factors that alter emotions trigger loss of sexual drive.